1983
DOI: 10.1002/jsfa.2740340608
|View full text |Cite
|
Sign up to set email alerts
|

Use of acid gel electrophoresis in the characterisation of ‘B’ hordein protein in relation to malting quality and mildew resistance of barley

Abstract: The 'B' polypeptides of the storage protein (hordein) of barley were studied in 84 varieties. On the basis of acid gel electrophoresis the varieties were classified into 13 distinct groups. Contrary to the suggestion that varieties preferred for malting tend to show less intensity of staining of the faster moving bands of the 'B' fraction of hordein, no consistent association was found in this study. Thus the malting potential of some varieties may be less affected by protein composition than by other factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The relationship between hordein and malting quality has been intensively investigated. Baxter and Wainwright 3 reported that B hordeins were related with malting quality, but a correlation was not found by Riggs et al 25 Peltonen et al 22 evaluated the effect of D, C, and B hordeins on malting quality of 19 spring barley cultivars and found that the B hordein fraction affected malting quality through regulating diastatic power. Howard et al 14 observed that the D hordein fraction was negatively correlated with malt extract, suggesting the existence of an association between D hordein and malting quality.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between hordein and malting quality has been intensively investigated. Baxter and Wainwright 3 reported that B hordeins were related with malting quality, but a correlation was not found by Riggs et al 25 Peltonen et al 22 evaluated the effect of D, C, and B hordeins on malting quality of 19 spring barley cultivars and found that the B hordein fraction affected malting quality through regulating diastatic power. Howard et al 14 observed that the D hordein fraction was negatively correlated with malt extract, suggesting the existence of an association between D hordein and malting quality.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that B hordein banding patterns may be of value as markers for improving malting quality traits of barley. Breeding for disease resistance in barley based on the B group of polypeptide markers has been attempted (SHEWRY et al 1979;RIGGS et al 1983). Patterns of B hordein are coded for by genes on chromosome 5 (FAULKS et al 1981;FIELD et al 1982;SHEWRY and MIFLIN 1982), and 0-amylase activity, by genes on chromosome 4 (JENSEN and NIELSEN 1984).…”
Section: Hordein Bands and Malting Qualitymentioning
confidence: 99%
“…Plant Sci. 67: 927-9U (Oct. 1987) (Shewry et al 1978a;Smith and Simpson 1983;Montembault et al 1983;Smith and Payne 1984;Heisel et al 1986) or PAGE at acid pH LaBerge 1980, 1981;Riggs et al 1983;Gebre et al 1986) provides the best resolution. Unfortunately, these methods suffer one major disadvantage in that a significant number of cultivars exhibit identical hordein electrophoregrams which render them indistinguishable.…”
mentioning
confidence: 99%